Research on Intelligent Large Slewing (International Journal of Information and Electronics Engineering, 2015)
There are many types of slewing ring, it is designed to both types of choices, but also by the size and structure of computing power, set the value of the non-expert planning, reasoning and numerical integration of scientific computing. Therefore, in the design of slewing expert system technology to break through the limitations of traditional analog design personal, integration experience of many experts in the design of a system to optimize the design of the structure, with significant engineering value. Based on the collection and analysis of full slewing design data and design experience, the establishment of a design expert system is as the core of the design, structural analysis and automatic drawing in one of the slewing ring Intelligent Design System - SRBID systems.